The Effect of Recombinant Vascular Endothelial Growth Factor (VEGF)-121 Towards Placenta Growth Factor Serum Levels in Female Mice (Mus Musculus) with Preeclampsia Model - Prabowo, Wisnu (Journal of Maternal and Child Health, 2021)
Background: Preeclampsia is a multi systemic disease which recognized by the development of hypertension after 20 weeks of gestation with the presence of proteinuria or any signs indicative of target organ injury. The correct diagnosis and classification of the disease are essential since the therapies are unique in each class. Moreover, the angiogenic factors claims to play a significant role in the endothelial injury which plays as an etiology for preeclampsia. Thus, this study aimed to analyze the differences between angiogenic factors in pregnancy mice with preeclampsia models after administration of VEGF-121. Subjects and Method: Subject of the study were swiss’s strains of pregnancy mice (Mus musculus) which divided into three groups that consist of 10 subject of study in each group. Subjects for this research were recruited between March and May 2015 in Biomedical Laboratory of The Faculty of Veterinary Medicine, Universitas Airlangga as part of a cross sectional study designed for analytical experimental. The angiogenic factor which measured was PIGF serum levels with ELISA method and only group of pregnant mice with preeclampsia model which administred with injection of VEGF-121. Results: This study was conducted of 30 male and 30 female Mus musculus with homogeneous characteristic in terms of age, average body weight and have never been pregnant before. The differences in PIGF serum levels between three observed group are significant (p=0.035). Conclusion: Administration of VEGF-121 increased the PlGF serum levels in pregnant mice with preeclampsia model. Thus, the administration of VEGF-121 improves the condition of endothelial damage in preeclampsia with an increase in PlGF levels.